Shear-induced anisotropy of granular materials with rolling resistance and particle shape effects. (1st October 2018) - Zhao, Shiwei; Evans, T. Matthew; Zhou, Xiaowen
Highlights: An elastoplastic rolling resistance model was employed to capture particle shape effect. Triaxial compression tests were simulated using superellipsoid-based DEM. Shear-induced fabric variation and anisotropy were examined during shear. Effects of rolling resistance and particle shape were comparatively investigated. Graphical abstract: Abstract: The rolling resistance model has been employed in the discrete element modelling in geomechanics, as an alternative computationally efficient approach to capture the resistance of particle rotation due to irregularity in shape. This paper presents a series of 3D DEM simulations of triaxial compression tests on specimens with rolling resistance and non-spherical particles using an in-house code. The non-spherical particle shapes are two kinds of special super-ellipsoids (i.e., superballs and ellipsoids) corresponding to two kinds of typical distortion in shape. A comprehensive comparison between the rolling resistance and particle shape effects on shear-induced fabric variation and anisotropy within granular materials is carried out. The simulations show that the manners in which quantifiers of fabric and anisotropy approach their respective critical state values vary with shear strain levels. Using the rolling resistance model can reproduce the main features of shear-induced fabric variation and anisotropy for most of these fabric measures. However, the effect of particle shape with just slight distortion from sphere can be captured well by the rolling resistance model. Moreover, high shear strengths can be achieved with sufficiently strong rolling resistance, but this is not recommended due to the unrealistic induced fabric. These findings highlight that the rolling resistance model should be carefully used in investigations, especially for micro-macro bridging.